Financial Crisis, the International Monetary System and the Challenge of the Emerging Economies - Rojas, Jorge (2011)
Although in the debate over the current financial crisis there is a general agreement on the role played by foreign capital inflows into the United States —that, together with financial deregulation, allowed for an excessive increase of credit in that country—, we think that their importance has not been fully appreciated, in terms of their link with the asymmetrical organization of an international monetary system that uses the dollar as a reserve currency, and their relationship with the economic growth model adopted by the US over the last thirty years; this relied on increased expenditure on the part of credit-financed households in order to maintain its dynamism, while inflation was kept down by importing cheap foreign manufactures at the expense of the domestic sector’s profitability. We suggest here that the crisis was related to the impossibility of maintaining this economic growth pattern indefinitely, and that recovery will require a radical reform of the international monetary system, as well as a general increase in economic efficiency.